DETERMINATION OF HEAT TECHNICAL PARAMETERS OF SOLAR WATER HEATING COLLECTORS (Archive of Conferences, 2022)
In the production of flat solar water heating collectors, a special place is occupied by thermal testing, the purpose of which is to determine their thermal characteristics experimentally.